2006
DOI: 10.1196/annals.1353.058
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling of Benign and Malignant Pheochromocytoma

Abstract: There are currently no reliable diagnostic and prognostic markers or effective treatments for malignant pheochromocytoma. This study used oligonucleotide microarrays to examine gene expression profiles in pheochromocytomas from 90 patients, including 20 with malignant tumors, the latter including metastases and primary tumors from which metastases developed. Other subgroups of tumors included those defined by tissue norepinephrine compared to epinephrine contents (i.e., noradrenergic versus adrenergic phenotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
53
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 16 publications
1
53
0
Order By: Relevance
“…Transcriptomic studies representing targets of miRNA-based regulation are pivotal for the correct interpretation of miRNA findings. There have been six previous studies 11,[37][38][39][40][41] on gene expression profiling involving malignant pheochromocytomas to date. The studies of Dahia et al, 11 Björklund et al 37 and the most recent study of Waldmann et al 41 included only two, three and five malignant pheochromocytomas, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Transcriptomic studies representing targets of miRNA-based regulation are pivotal for the correct interpretation of miRNA findings. There have been six previous studies 11,[37][38][39][40][41] on gene expression profiling involving malignant pheochromocytomas to date. The studies of Dahia et al, 11 Björklund et al 37 and the most recent study of Waldmann et al 41 included only two, three and five malignant pheochromocytomas, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The studies of Dahia et al, 11 Björklund et al 37 and the most recent study of Waldmann et al 41 included only two, three and five malignant pheochromocytomas, respectively. Brouwers et al 38 examined 20 malignant tumors along with 70 sporadic and syndromic benign tumors: Gene Ontology Analysis of benign and malignant tumor comparison revealed the relevance of signal transduction changes. The significant gene sets established in two recent large-scale studies by Thouënnon et al 39 and Suh et al 40 are quite different, which indicates the need for further, large-scale gene expression profiling studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, our analysis of a huge PHEO microarray database with 70 benign and 20 malignant metastatic specimens has shown that up to 89% of genes were under-expressed in malignant primary tumors as compared to benign tumors (23). Interestingly, further detailed analysis of this database also revealed a differential expression of neuropeptide hormone receptors in subtypes of human PHEO.…”
mentioning
confidence: 95%
“…The incidence in the general population is estimated to be less than 1 per 100,000 people per year [3]. The majority of PH are benign, while malignant tumors occur in about 10% of PH [4]. The most common metastatic sites for chromaffin cell tumors are local lymph nodes, bone, liver, and lung [5,6].…”
Section: Introductionmentioning
confidence: 99%